2021
DOI: 10.1021/acs.jproteome.0c00990
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Pancreatic Cancer in Type 2 Diabetes Mellitus Patients Based on 1H NMR Metabolomics

Abstract: The association of pancreatic cancer with type 2 diabetes mellitus was investigated by 1H NMR metabolomic analysis of blood plasma. Concentration data of 58 metabolites enabled discrimination of pancreatic cancer (PC) patients from healthy controls (HC) and long-term type 2 diabetes mellitus (T2DM) patients. A panel of eight metabolites was proposed and successfully tested for group discrimination. Furthermore, a prediction model for the identification of at-risk individuals for future development of pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 42 publications
(121 reference statements)
0
29
0
Order By: Relevance
“…Proline is one of the nonessential amino acids, which has been shown that it can be used as the main carbon source by pancreatic cancer to maintain mitochondrial function and the TCA cycle ( 30 , 31 ). A decrease of proline level in PDAC has been reported in several studies, which may indicate the vigorous metabolism of pancreatic cancer cells ( 27 , 32 , 33 ).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Proline is one of the nonessential amino acids, which has been shown that it can be used as the main carbon source by pancreatic cancer to maintain mitochondrial function and the TCA cycle ( 30 , 31 ). A decrease of proline level in PDAC has been reported in several studies, which may indicate the vigorous metabolism of pancreatic cancer cells ( 27 , 32 , 33 ).…”
Section: Discussionmentioning
confidence: 79%
“…Michálková et al. ( 27 ) used 1 H NMR metabolomic analysis to discriminate PDAC patients from healthy controls and also from T2DM by plasma samples. Isoleucine was found increased in T2DM, but without statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Out of them, two metabolites namely N-Succinyl-L-diaminopimelic-acid and PE (18: 2) had shown good sensitivity (93.3%) and specificity (93.1%) for PC in the logistic regression analysis. A recent nuclear magnetic resonance based study also identified a panel of eight metabolites with good accuracy (more than 80%) in the discrimination of PC and long-standing T2DM patients[ 112 ]. In future, possibly a panel of metabolites will help us to improve the precision medicine in identifying the cases requiring close follow-up for detection of PC among diabetes patients.…”
Section: Biomarkers In the Screening Of Pc In Dmmentioning
confidence: 99%
“…In this sense, Nuclear Magnetic Resonance (NMR) spectroscopy was shown to be a powerful technique for the high-throughput analysis of blood samples [19,20]. NMR spectroscopy has been used to investigate the serum metabolome of patients with PDAC to distinguish malignant and benign diseased states and some metabolites, such as leucine, valine, isoleucine, tyrosine, lysine, creatinine, triglycerides, and 3-hydroxybutyrate, were dysregulated [21][22][23][24]. Although these authors reported the blood-based metabolomics biomarkers of PDAC, their findings did not make associations to outcomes and were conducted in other population groups [25,26].…”
Section: Introductionmentioning
confidence: 99%